The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1126/scitranslmed.aax0481
|View full text |Cite
|
Sign up to set email alerts
|

Platelet regulation of myeloid suppressor of cytokine signaling 3 accelerates atherosclerosis

Abstract: Platelets are best known as mediators of hemostasis and thrombosis; however, their inflammatory effector properties are increasingly recognized. Atherosclerosis, a chronic vascular inflammatory disease, represents the interplay between lipid deposition in the artery wall and unresolved inflammation. Here, we reveal that platelets induce monocyte migration and recruitment into atherosclerotic plaques, resulting in plaque platelet-macrophage aggregates. In Ldlr−/− mice fed a Western diet, platelet depletion decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
88
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(101 citation statements)
references
References 83 publications
6
88
0
2
Order By: Relevance
“…Moreover, the CBC cannot account for specific markers and their expression levels on subpopulations of white blood cells, nor will it allow the identification and quantification of different monocyte subpopulations or NK cells. Also, the CBC cannot account for 'hitchhiking' platelets, which are associated with CVD risk [31,[40][41][42], especially highlighted in a recent study focusing on women [43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the CBC cannot account for specific markers and their expression levels on subpopulations of white blood cells, nor will it allow the identification and quantification of different monocyte subpopulations or NK cells. Also, the CBC cannot account for 'hitchhiking' platelets, which are associated with CVD risk [31,[40][41][42], especially highlighted in a recent study focusing on women [43].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the quality and quantity of platelet adhesion differs between the various immune cells [57,58]. Very recently, Barrett et al demonstrated that platelet adhesion on monocytes in mice promoted an inflammatory and proatherogenic phenotype accompanied by increased leukocyte trafficking and macrophage accumulation within the atherosclerotic plaque [43]. Utilizing human samples, Barrett et al also showed a positive correlation of monocyte-platelet aggregates with atherosclerosis severity in two cohorts, including a cohort of women with or without myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
“…In atherosclerosis, cytokine-mediated cell activation and expression of endothelial cell adhesion molecules contribute to the innate immune response ( 1 ). Platelet-endothelial interactions have also been shown to promote plaque development even at early stages of disease, most likely through proinflammatory effects of the platelet secretome, direct effects on macrophage subtype, or by serving as an alternative binding partner for leukocytes ( 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ). In vivo molecular imaging has recently been used to confirm histological findings that arterial platelet adhesion in atherosclerosis is mediated by increased endothelial-associated von Willebrand factor (vWF) and exposure of the vWF A1 binding domain for the glycoprotein-Ibα (GPIbα) subunit of the platelet GPIb-IX-V complex ( 10 , 11 , 12 ).…”
mentioning
confidence: 99%
“…In addition, SOCS3 was reported as an anti-inflammatory cytokine ( 37 ) that affects cardiac function via various inflammatory cytokines; SOCS3 deficiency in the heart promotes cardiac hypertrophy by enhancing the JAK/STAT activity induced by IL-6 ( 38 ); SOCS3 deficiency in T cells increases IL-17 production and reduces atherosclerotic lesion development and vascular inflammation, whereas overexpression of SOCS3 in T cells reduces IL-17 and accelerates atherosclerosis ( 39 ). Moreover, Barrett et al ( 40 ) demonstrated that platelets promoted the development of atherosclerosis by increasing an inflammatory phenotype of plaque macrophages and SOCS3 expression. In vitro , we found a significant upregulation of SOCS3 during the progression of THP-1 foam cell formation, which is in stark contrast to the decreasing trend seen in the leukocytes of CAD patients.…”
Section: Discussionmentioning
confidence: 99%